Supporting Young People’s Mental Health: Reconceptualizing the Role of Schools or a Step Too far? - Glazzard, Jonathan; Stones, Samuel (Frontiers in Education, 2021)
This article provides an overview of the United Kingdom government’s strategy for children’s mental health in schools. Critique of the mental health policy document demonstrates that the government has adopted a clinical approach to resolving the mental health “crisis” among children and young people. We argue that a clinical solution, implemented in schools, is not based on robust evidence and that the policy reflects a medical model which positions children and young people with mental ill health through a deficit lens. We argue that the government should, instead, adopt a systemic response which directly addresses the underlying factors which cause mental ill health rather than implementing a clinical approach in schools. We argue that a clinical response at the level of the individual is not appropriate for most children and young people with mental ill health and that there needs to be an urgent review of policy.